2017
DOI: 10.1186/s40409-017-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal effects of scorpion venoms: maternal and offspring development

Abstract: Scorpion envenomation is a public health problem, especially in tropical and subtropical countries. Considering the high incidence of scorpionism in some areas, pregnant women and nursing mothers may be possible victims. Scorpion stings alter the release of neurotransmitters and some cytokines. These mediators act as organizers and programmers in the adequate formation of the nerves, and non-physiological concentrations of them during the brain organization originate disorders and diseases that can appear late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Despite its importance, there is insufficient information on the effects of scorpion envenomation on pregnancy and neonatal outcomes, and unfortunately the available data is controversial [23]. Therefore, the present study aimed to assess the possible toxic effects of scorpionism on pregnancy and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite its importance, there is insufficient information on the effects of scorpion envenomation on pregnancy and neonatal outcomes, and unfortunately the available data is controversial [23]. Therefore, the present study aimed to assess the possible toxic effects of scorpionism on pregnancy and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Some previous studies in Khuzestan province in Iran have reported that most scorpion-sting victims were female homemakers [11,22]. However, the available medical data on the effects of the scorpion envenomation on pregnancy outcomes are not only insufficient but also somewhat controversial [23]. The aim of the present study was to examine the effect of scorpion envenomation on pregnancy outcomes, maternal and prenatal-neonatal complications, in pregnant women referred to the Clinical Toxicology Unit of Ahvaz Razi Hospital (Khuzestan province, southwestern Iran).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this weed cum herb is widely cultivated and used as a vegetable and fruit in Malaysia (locally known as rumput sambau) and other tropical and subtropical regions of the globe. The positive part of the weed has lots of traditional medicinal uses, including leaves used for microbial infection, muscle pain, cough, scorpion poisoning, hastening the delivery of placentas for women after the birth of a baby, and relieving pain during vaginal bleeding (Dorce et al, 2017;Sukor et al, 2023). The root extracts are widely used for the treatment of asthma; whole plant extracts for urinary infection; areal plant extracts with rice are also used for flu viral infection; and root extracts with Capsicum sp.…”
Section: Introductionmentioning
confidence: 99%
“…(Solanacae) for piles. From several recent scientific investigations, exhibited antioxidant, antidiabetic, antibacterial, anticonvulsant, anti-inflammatory, hepatoprotective, antipyretic, analgesic, etc., activities (Dorce et al, 2017;Ogbole et al, 2027;Puah et al, 2022). In addition, a few active phytochemicals, like hexanoic acid, sioschaftoside, sitosterol, stigasterol, isovitexin, vitexin, coumatin, etc., have been identified through column-chromatography, gas chromatography-mass spectrometry (GCMS), and liquid chromatography-mass spectrometry (LCMS) approaches (Ong et al, 2016;Sukor et al, 2023).…”
Section: Introductionmentioning
confidence: 99%